1995
DOI: 10.1002/j.1460-2075.1995.tb00107.x
|View full text |Cite
|
Sign up to set email alerts
|

RNA polymerase alpha subunit binding site in positively controlled promoters: a new model for RNA polymerase-promoter interaction and transcriptional activation in the Escherichia coli ada and aidB genes.

Abstract: The ada and aidB genes are part of the adaptive response to DNA methylation damage in Escherichia coli. Transcription of the ada and the aidB genes is triggered by binding of the methylated Ada protein (meAda) to a specific sequence located 40–60 base pairs upstream of the transcriptional start, which is internal to an A/T‐rich region. In this report we demonstrate that the Ada binding site is also a binding site for RNA polymerase. RNA polymerase is able to bind the −40 to −60 region of the ada and the aidB p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 27 publications
5
44
0
Order By: Relevance
“…Although RNAP is bound to the malT promoter, CRP might be required to accelerate the formation of the open complex (43). Similarly, Ada does not enhance RNAP binding to the ada and aidB promoters but instead stimulates transcription by stabilizing an intermediate RNAP-promoter complex (44). Involvement of the ␣-CTD in the transition from closed to intermediate complexes was also proposed as the role of the p4 protein in activation at the phage phi29 A3 promoter (45).…”
Section: Discussionmentioning
confidence: 99%
“…Although RNAP is bound to the malT promoter, CRP might be required to accelerate the formation of the open complex (43). Similarly, Ada does not enhance RNAP binding to the ada and aidB promoters but instead stimulates transcription by stabilizing an intermediate RNAP-promoter complex (44). Involvement of the ␣-CTD in the transition from closed to intermediate complexes was also proposed as the role of the p4 protein in activation at the phage phi29 A3 promoter (45).…”
Section: Discussionmentioning
confidence: 99%
“…The DNA promoter region shows characteristics of a promoter UP element, which are constituted by AT-rich regions of 20 bp spanning from ¹40 to ¹60 with a possible non-perfect inverted repeat. It has been demonstrated that these UP elements are the target sites of the C-terminal domain ᮊ 1997 Blackwell Science Ltd, Molecular Microbiology, 26, 361-372 of the ␣-subunit of RNA polymerase, thereby enhancing transcription (Ross et al, 1993;Attey et al, 1994;Landini and Volkert, 1995). In the case of the rrnB P 1 promoter of E. coli, interaction of ␣ with the UP element enhances promoter activity by approximately 30-fold (Ross et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…At this promoter, truncation of RNA polymerase ␣CTD, or substitution of its R265 residue by alanine, abolishes ␣ binding to the UP element (14). These mutations also affect RNA polymerase binding to the Ϫ60 to Ϫ40 region of ada and aidB and impair transcription initiation (26). Based on these observations, the Ϫ60 to Ϫ40 regions of ada and aidB are functionally similar to the rrnB UP element and they are sufficient to recruit RNA polymerase.…”
Section: Mechanism Of Transcription Activation By Me Adamentioning
confidence: 97%
“…The evidence for this model was based on the observation that truncations in ␣CTD abolish transcription from the ada promoter in the presence of me Ada. However, more recent data indicate that RNA polymerase binds to the Ϫ60 to Ϫ40 region of the ada and aidB promoters via its ␣CTD, regardless of the presence of Ada (26). This region serves as the me Ada binding site, but it also closely resembles, in AϩT content, location, and function, the UP element transcription enhancer sequence identified in the rrnBP1 promoter (49).…”
Section: Mechanism Of Transcription Activation By Me Adamentioning
confidence: 99%
See 1 more Smart Citation